PERSEPSI PUBLIK TERHADAP KINERJA PEMERINTAH KOTA PEKANBARU DALAM PENGENDALIAN BANJIR TAHUN 2015-2017 - Putri, Sandra Setia; Wicaksono, Baskoro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
The city of Pekanbaru has a densely populated population of more than one million people. Along with the development of the city of Pekanbaru into a Metropolitan City, it is inseparable from various problems that arise, namely the problem of flooding. The problem of flooding is a problem that does not resolve every year. This was caused by the development of Pekanbaru City which was not followed by adequate flood control infrastructure systems. In this case, of course, the public spotlight on the performance of the government in overcoming flood problems in the city of Pekanbaru. The formulation of the problem in this study is What is the public perception of the performance of the Pekanbaru City Government in 2015-2017 Flood Control?This study aims to find out how public perceptions of the performance of the Pekanbaru City Government in flood control in 2015-2017 are seen from aspects: (1) Productivity, (2) Service Quality, (3) Responsiveness, (4) Responsibility, and (5) Accountability. This research is a descriptive study using the Mixed Method approach. The data collection technique in this study is to use a survey technique by taking a sample of 100 people from one population using a questionnaire as a means of collecting basic data and using interview techniques with as many as 10 informants. Data analysis used for quantitative methods is quantitative analysis and analysis for qualitative methods using qualitative analysis, and finally is analyzing data combined with qualitative analysis and quantitative analysis.The results of the study concluded that public perception regarding the performance of the Pekanbaru City Government in 2015-2017 flood control was still not good. This is shown from the results of the average value of each indicator (productivity, service quality, responsiveness, responsibility, and accountability) which is equal to 1.95 which is in the range of 1.76 - 2.50 which shows unfavorable criteria. In this case the public considers that the Pekanbaru City Government has not been able to optimize the implementation of flood control in Pekanbaru City.Keywords: Public Perception, Performance of Pekanbaru City Government, Flood Control